2020
DOI: 10.1016/j.apsusc.2019.145235
|View full text |Cite
|
Sign up to set email alerts
|

Local removal of silicon layers on Si(1 0 0)-2 × 1 with chlorine-resist STM lithography

Abstract: We report the realization of STM-based lithography with silicon layers removal on the chlorinated Si(100)-2×1 surface at 77 K. In contrast to other STM lithography studies, we were able to remove locally both chlorine and silicon atoms. Most of the etched pits have a lateral size of 10-20Å and a depth of 1-5Å. In the pits in which the STM image with atomic resolution is obtained, the bottom is mainly covered with chlorine. Some pits contain chlorine vacancies. Mechanisms of STMinduced removal of silicon and ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Apart from H-saturated surfaces, alternative resists like halogen atoms, native oxides [41], and molecules [42] have been used to manufacture atomic devices [43]. Halogens have attracted the most attention, and promising results have been demonstrated in recent studies [44,45]. Similar applications with HDL could be seen in the manufacturing of next-generation nano devices such as single-electron transistors [46], quantum computer qubits [47][48][49], editable atomic-scale memories [50], and two-dimensional quantum metamaterials [51].…”
Section: Research Statusmentioning
confidence: 99%
“…Apart from H-saturated surfaces, alternative resists like halogen atoms, native oxides [41], and molecules [42] have been used to manufacture atomic devices [43]. Halogens have attracted the most attention, and promising results have been demonstrated in recent studies [44,45]. Similar applications with HDL could be seen in the manufacturing of next-generation nano devices such as single-electron transistors [46], quantum computer qubits [47][48][49], editable atomic-scale memories [50], and two-dimensional quantum metamaterials [51].…”
Section: Research Statusmentioning
confidence: 99%
“…By studying the DBs on the silicon surface terminated by halogens (Hal = Cl, Br), we make a step toward the DBs applications on the technologically relevant Si(100)-2×1-Hal surface. Recently, the Si(100)-2×1-Hal surface has attracted research interest as a potential platform for the development of quantum devices with single impurities [23][24][25][26][27] . As well as hydrogen, halogens can be utilized as a resist on a silicon surface 26,27 and, in addition, halogen resist is compatible with the Hal-containing dopants 24 .…”
Section: Introductionmentioning
confidence: 99%
“…As well as hydrogen, halogens can be utilized as a resist on a silicon surface 26,27 and, in addition, halogen resist is compatible with the Hal-containing dopants 24 . Previously, it was shown that a strong Si-Cl bond allows desorption of Cl atoms together with Si atoms 25 with the further goal of creating individual SiCl vacancies 23 . In order to modify the halogenated Si(100) surface with atomic precision, the creation of single DBs is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the ADTP as a template for atomic-precision dopant placement raises important questions regarding the use of large halogen adatoms as a resist. Only recently has Cl-Si(100) been explored for atomic precision fabrication applications [20][21][22] and the differences between halogens and hydrogen present a few unknowns. In particular, the increased size of halogen adsorbates relative to hydrogen promote steric hindrances that not only foster the selfassembled resist pattern discussed here, but may also play a role in hindering adsorption into a SDW.…”
Section: Introductionmentioning
confidence: 99%